2010
DOI: 10.1007/s00468-010-0511-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of re-integrated Ac element positions in the genome of Populus provides a basis for Ac/Ds-transposon activation tagging in trees

Abstract: With a view to establish an efficient gene tagging system for forest tree species, we assessed the transposition behaviour of the maize transposable element Ac in poplar. In earlier work, we showed that new integration sites were often located within predicted or known coding sequences. However, somatic transposition behaviour of Ac with regard to conserved chromosome specificity or, more specifically, whether Ac transposition is restricted to the chromosome on which the primary insertion locus (donor) is loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…This proposal was based on the fact that the maize transposable element Ac is functional in the Populus genome [24], and re-integrations occur at high frequencies in or near coding regions [23]. Further, the majority of re-integrations were found scattered over many unlinked sites on other scaffolds than the one carrying the original integration locus, confirming that Ac does in fact cross chromosome boundaries in poplar [25]. …”
Section: Introductionmentioning
confidence: 99%
“…This proposal was based on the fact that the maize transposable element Ac is functional in the Populus genome [24], and re-integrations occur at high frequencies in or near coding regions [23]. Further, the majority of re-integrations were found scattered over many unlinked sites on other scaffolds than the one carrying the original integration locus, confirming that Ac does in fact cross chromosome boundaries in poplar [25]. …”
Section: Introductionmentioning
confidence: 99%
“…The global transposition of Ds observed among our T 1 transposon‐tagged lines is a distinct advantage over systems where mostly local transposition has been described as with poplar (Fladung, 2011). However, an efficient system depends heavily on reliable selection to eliminate FDS plants and isolate Ds plants.…”
Section: Discussionmentioning
confidence: 74%
“…The EDS and the NPTII (Ds) should segregate in the T 2 generation after self-pollination of T 1 , provided the absence of tight linkage between them or that EDS was not homozygous owing to its potential segregation during both male and female gametogenesis of our T 0 lines. The global transposition of Ds observed among our T 1 transposon-tagged lines is a distinct advantage over systems where mostly local transposition has been described as with poplar (Fladung, 2011). However, an efficient system depends heavily on reliable selection to eliminate FDS plants and isolate Ds plants.…”
Section: Discussionmentioning
confidence: 87%
“…It could be shown that the maize transposable element Ac is functional in the Populus genome [3], and re-integrations occur in high frequencies in or near coding regions [4]. Further, the majority of the re-integrations were found scattered over many unlinked sites on other scaffolds than the one carrying the original integration locus, confirming that Ac does in fact cross chromosome boundaries in poplar [5]. …”
Section: Methodsmentioning
confidence: 99%